Recombinant adenylate kinase 3 from liver fluke Clonorchis sinensis for histochemical analysis and serodiagnosis of clonorchiasis. Issue 12 (27th March 2018) - Kwon, Soon Bin; Kim, Paul; Woo, Hae Sun; Kim, Tae Yun; Kim, Ju Yeong; Lee, Hye Min; Jang, Yun Soo; Kim, Eun-Min; Yong, Tai-Soon; Seong, Baik Lin
Abstract: Due to the lack of an effective prophylactic intervention and diagnosis, human liver fluke Clonorchis sinensis continues to afflict a large human population, causing a chronic inflammatory bile duct disease. With an aim to identify target antigens for sensitive serodiagnosis, adenylate kinase 3 of C. sinensis (CsAK3) was successfully expressed in soluble form in Escherichia coli by fusion to an RNA-interacting domain derived from human Lys-tRNA synthetase and purified by Ni 2+ -affinity chromatography. Anti-CsAK3 serum was raised by immunization of mice, and Western blotting confirmed that CsAK3 was expressed in adult-stage C. sinensis . Histochemical analysis showed that CsAK3 was localized to the subtegumental tissue of C. sinensis and was excreted into the bile duct of the host. When tested against sera from various parasite-infected patients by enzyme-linked immunosorbent assay, the recombinant CsAK3 elicited a specific response to C. sinensis -infected sera. The results suggest that CsAK3, either alone or in combination with other antigens, could be used for improving the clinical diagnosis of clonorchiasis.